Treatment of Whiplash-Associated Disorders - Part II: Medical and Surgical Interventions. (1st March 2005) - Conlin, Anne; Bhogal, Sanjit; Sequeira, Keith; Teasell, Robert
Abstract : BACKGROUND: Whiplash-associated disorder (WAD) is a term used to describe injury due to an acceleration-deceleration mechanism at the neck. In 1995, the Quebec Task Force published a report that contained evidence-based recommendations regarding the treatment of WAD based on studies completed before 1993 and consensus-based recommendations. OBJECTIVE: The objective of the present article - the second installment of a two part review on WAD - is to provide a systematic review of the literature published between January 1993 and July 2003 on medical and surgical interventions for WAD using meta-analytical techniques. METHODS OF THE REVIEW: Three medical literature databases were searched for identification of all clinical trials on the treatment of WAD. Randomized controlled trials (RCTs) and epidemiological studies were categorized by treatment modality and analyzed by outcome measures. The methodological quality of the RCTs was assessed. When possible, pooled analyses of the RCTs were completed for meta-analyses of the data. The results of all the studies were compiled and systematically reviewed. RESULTS: The studies were categorized as medical or surgical interventions. A total of five RCTs and six non-RCTs were evaluated. The mean methodological quality of the RCTs was 7.3 among studies on medical interventions and 7.5 for studies on surgical intervention. Pooled analyses were completed across all treatment modalities and outcome measures. The outcomes of each study were summarized in tables. CONCLUSIONS: While several quality RCTs and epidemiological studies have been published since 1993 on medical and surgical interventions, the cumulative evidence is lacking. Moderate evidence exists in support of radiofrequency neurotomy. Evidence for steroid injections, botulinum treatments, carpal tunnel decompression and cervical discectomy is conflicting or unclear. Future research is required to clarify the utility of radiofrequency neurotomy and pulsed electromagnetic field treatment for WAD.